2006
DOI: 10.1007/s00203-006-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone-induced expression of recombinant proteins in Streptococcus thermophilus

Abstract: A locus encoding proteins with high homology to the pneumococcal BlpABCHR quorum-sensing system was identified in Streptococcus thermophilus LMG 18311. The BlpABCHR system regulates bacteriocin production in Streptococcus pneumoniae by monitoring the extracellular concentration of a peptide-pheromone encoded by blpC. The homologous system in S. thermophilus, termed StbABCHR, contains a corresponding gene (stbC) encoding a possible peptide-pheromone (STP) that presumably controls bacteriocin production in S. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In agreement with this observation, transcriptome analyses suggest that BlpC St regulates the transcription of only genes located within the blp St locus of S. thermophilus LMD-9 (data not shown). In the course of the present study, Blomqvist et al (7) showed that a reporter fusion between the blpU St LMG18311 promoter and gusA was induced 10-fold by the predicted mature form of BlpC St LMG18311 in S. thermophilus LMG18311. These authors reported that the complete deletion of the DR motif from blpU St LMG18311 abolished the BlpC St -dependent induction of glucuronidase activity, further supporting the hypothesis that the DR motif is the binding site of BlpR St .…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…In agreement with this observation, transcriptome analyses suggest that BlpC St regulates the transcription of only genes located within the blp St locus of S. thermophilus LMD-9 (data not shown). In the course of the present study, Blomqvist et al (7) showed that a reporter fusion between the blpU St LMG18311 promoter and gusA was induced 10-fold by the predicted mature form of BlpC St LMG18311 in S. thermophilus LMG18311. These authors reported that the complete deletion of the DR motif from blpU St LMG18311 abolished the BlpC St -dependent induction of glucuronidase activity, further supporting the hypothesis that the DR motif is the binding site of BlpR St .…”
Section: Discussionmentioning
confidence: 47%
“…These authors reported that the complete deletion of the DR motif from blpU St LMG18311 abolished the BlpC St -dependent induction of glucuronidase activity, further supporting the hypothesis that the DR motif is the binding site of BlpR St . Additionally, various mutations in the left repeat, the right repeat, and the spacer of the DR motif affected induction of the promoter by BlpC St (7). In this context, the observed differences in the strength of the response to BlpC St among the DR-containing blp St operons blpD St -orf2, blpE-F St , blpU St -orf3, and blpABC St might result from different affinities of the regulatory protein BlpR St for the corresponding promoters as a consequence of mutations in the DR motif (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gut HGT and natural competence are likely to have played a major role in the evolution and ecology of the microbiota as well as strain diversity [8]. The competent state of “DNA receptivity” is controlled by a large, dispersed set of genes encoding proteins responsible for DNA uptake and recombination, as well as other processes related to competence induced cell stress [9], [10], [11], [12], [13], [14]. Homologues of competence genes are widespread among bacteria that have not yet been demonstrated to be naturally transformable, suggesting that the mechanism may in fact be more common, especially within the phyla that contain members that are already known to be naturally competent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been shown that the luciferase of Photorhabdus luminescens (Fontaine et al, 2010aGardan et al, 2013) and the green fluorescent protein gene of the jellyfish Aequorea victoria (Solaiman and Somkuti, 1997a;Somkuti and Steinberg, 1999;Renye and Somkuti, 2009) were both functional in S. thermophilus. This is also the case for the gusA gene of E. coli which confers the b-glucuronidase activity (Mora et al, 2005;Blomqvist et al, 2006b;Liu et al, 2009;Chang and Yan, 2014) or the gene encoding the a-galactosidase of Lc.…”
Section: Available Selection Markersmentioning
confidence: 95%